Biophysical and biochemical changes in tomato (Solanum lycopersicum) genotypes at different fruit developmental stages under protected cultivation - KUMAR, SONA; KRISHNAN, P; SINGH, P K; VASHISTH, ANANTA; KUNDU, MONIKA (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during 2020–21 and 2021–22 to evaluate the biophysical and biochemical characteristics of tomato [Solanum lycopersicum (L.)] genotypes (Pusa Rohini, Pusa Cherry-1, S-22, PKM-1 and Pusa Protected-1) grown at Centre for Protected Cultivation Technology (CPCT), ICAR-Indian Agricultural Research Institute, New Delhi. Tomato fruits were harvested at 14 different fruit developmental stages (DS01-DS14) starting from 4 days after post anthesis to the final red riped stage. Fruit size (length and width), biomass, firmness, total soluble solids (TSS), titratable acids (T.A), β-carotene, ascorbic acid and lycopene content were analysed for all the developmental stages. The highest value of fruit length, breadth, biomass, TSS, β-carotene and lycopene content was observed at full ripe tomatoes and the lowest in the early immature green stage. However, parameters like fruit firmness,T.A and ascorbic acid content were higher in early immature to mature green stage and decreased once the fruit entered the ripening stage. Thus, irrespective of the genotypes considered in this study, all the above parameters except fruit firmness, ascorbic acid and T.A were found to increase gradually with the advancement of ripening process. This clearly showed a significant relationship between the biochemical and biophysical parameters of the tomatoes with their fruit developmental stages, hence could be used as an indicator to characterize the fruit developmental stages.